2000
DOI: 10.1176/appi.ajp.157.4.632
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Dopamine Activity in the Basal Ganglia of Cigarette Smokers

Abstract: Smoking is related to greater dopamine activity in the human basal ganglia. Nicotine-induced dopamine activity may be a relevant mechanism in dependence on cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 13 publications
6
88
2
3
Order By: Relevance
“…In addition, smokers showed stronger T reflex magnitudes during rest, indicating increased sensitivity of the somatic motor system in smokers. These findings are in line with evidence for changes in dopaminergic systems and reward processing as a result of tobacco use (eg Martin-Sölch et al, 2001;Rose et al, 2003;Salokangas et al, 2000), and with evidence for increased locomotor activity after changes in the mesolimbic dopamine system by nicotine administration in rats (eg Ferrari et al, 2001). The observed differences between smokers and nonsmokers in the present study underline the importance to record smoking status in studies on the effect of dopamine on appetitive responses in humans.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, smokers showed stronger T reflex magnitudes during rest, indicating increased sensitivity of the somatic motor system in smokers. These findings are in line with evidence for changes in dopaminergic systems and reward processing as a result of tobacco use (eg Martin-Sölch et al, 2001;Rose et al, 2003;Salokangas et al, 2000), and with evidence for increased locomotor activity after changes in the mesolimbic dopamine system by nicotine administration in rats (eg Ferrari et al, 2001). The observed differences between smokers and nonsmokers in the present study underline the importance to record smoking status in studies on the effect of dopamine on appetitive responses in humans.…”
Section: Discussionsupporting
confidence: 80%
“…There is evidence from research on rats that nicotine affects dopaminergic function (eg Ferrari et al, 2001;Trauth et al, 2001), and in humans smoking has been related to greater dopamine activity in the basal ganglia (Salokangas et al, 2000). To investigate smoking as a possible mediating variable in the effect of levodopa on somatic motor activity, smokers and nonsmokers were compared on T reflex magnitude during sexual stimulation.…”
Section: Additional Analysesmentioning
confidence: 99%
“…Other functional imaging studies of the DA system have reported decreased D1 receptor density (Dagher et al, 2001), increased 18 F-DOPA uptake (a marker for increased DA turnover) (Salokangas et al, 2000a), and both decreased (Krause et al, 2002) and no alterations (Staley et al, 2001) in dopamine transporter binding in smokers.…”
Section: Brain Dopamine Responses To Nicotine and Smokingmentioning
confidence: 92%
“…In humans, tobacco use has been associated with both increased striatal dopamine synthesis capacity (Salokangas et al, 2000) and dopamine release in response to acute cigarette use in smokers (Brody et al, 2004;Le Foll et al, 2013). However, two studies found that acute nicotine use did not elicit a significant dopamine release in smokers (Barrett et al, 2004;Montgomery et al, 2007), although these did find that the subjective hedonic response to acute nicotine was related to dopamine release.…”
Section: Introductionmentioning
confidence: 94%